(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
This article reveals the competency-based approaches to preparing students of higher education institutions for management activities. Because today, it is very important to properly organize management activities in the process of professional activity and create a friendly environment for working together with personnel as a team. Therefore, in higher education, students should be instilled with knowledge and skills of management competence in the development of professional skills. Practical skills are developed and improved in working with a team in labor activities.